2006
DOI: 10.4161/hv.2.2.2555
|View full text |Cite
|
Sign up to set email alerts
|

Live Attenuated Chimeric Yellow Fever Dengue Type 2 (ChimeriVax™-DEN2) Vaccine: Phase I Clinical Trial for Safety and Immunogenicity: Effect of Yellow Fever Pre-immunity in Induction of Cross Neutralizing Antibody Responses to All

Abstract: A randomized double-blind Phase I Trial was conducted to evaluate safety, tolerability, and immunogenicity of a yellow fever (YF)-dengue 2 (DEN2) chimera (ChimeriVax™-DEN2) in comparison to that of YF vaccine (YF-VAX ® ). Forty-two healthy YF naïve adults randomly received a single dose of either ChimeriVax™-DEN2 (high dose, 5 log plaque forming units [PFU] or low dose, 3 log PFU) or YF-VAX ® by the subcutaneous route (SC). To determine the effect of YF preimmunity on the ChimeriVax TM -DEN2 vaccine, 14 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
137
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(141 citation statements)
references
References 30 publications
(39 reference statements)
2
137
0
2
Order By: Relevance
“…Recent clinical studies have indicated that antigenic chimeric flaviviruses are attenuated and immunogenic in human volunteers and may serve as live attenuated virus vaccines for protection against disease caused by DEN, JE, WN, and TBE viruses [27][28][29][30][31]. These positive results observed in several clinical trials support the further development and study of antigenic chimeric flaviviruses.…”
Section: Discussionmentioning
confidence: 87%
“…Recent clinical studies have indicated that antigenic chimeric flaviviruses are attenuated and immunogenic in human volunteers and may serve as live attenuated virus vaccines for protection against disease caused by DEN, JE, WN, and TBE viruses [27][28][29][30][31]. These positive results observed in several clinical trials support the further development and study of antigenic chimeric flaviviruses.…”
Section: Discussionmentioning
confidence: 87%
“…Because of the important role of neutralizing antibodies as surrogates of protection, the validation of neutralization tests is a priority 128 . Current approaches to vaccine development involve using live attenuated viruses, inactivated viruses, subunit vaccines, DNA vaccines, cloned engineered viruses and chimeric viruses using yellow fever vaccine and attenuated dengue viruses as backbones [129][130][131][132][133][134] . TABLE 1 summarizes the most advanced vaccine candidates.…”
Section: Vaccine Developmentmentioning
confidence: 99%
“…Attenuation of YFV-17D has been attributed to mutations in the YFV-17D envelope protein, which may hinder spread of the virus to visceral tissues, and was recently linked to reduced quasispecies diversity (Beck et al, 2014;Hahn et al, 1987;Lee & Lobigs, 2008). Considering that YFV-17D is currently being used in chimeric vaccines to JEV, and for the development of vaccines to WNV and DENV, a better understanding of its attenuation is imperative (Guirakhoo et al, 2006;Guy et al, 2010;Monath et al, , 2006Pugachev et al, 2005).…”
Section: Introductionmentioning
confidence: 99%